2021
DOI: 10.1136/bmjopen-2020-046701
|View full text |Cite
|
Sign up to set email alerts
|

Hormone replacement therapy and cancer survival: a longitudinal cohort study: protocol paper

Abstract: IntroductionHormone replacement therapy (HRT) can help women experiencing menopausal symptoms, but usage has declined due to uncertainty around risks of cancer and some cardiovascular diseases (CVD). Moreover, improved cancer survival rates mean that more women who survive cancer go on to experience menopausal symptoms. Understanding these relationships is important so that women and their clinicians can make informed decisions around the risks and benefits of HRT. This study’s primary aim is to determine the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 51 publications
0
3
0
1
Order By: Relevance
“…Currently used hormone replacement therapy consists of estrogen pills for hysterectomized women and estrogen-progestin combinations for the rest [19,20]. Estrogen helps alleviate menopausal symptoms, while progestin prevents estrogen-induced proliferation of uterine epithelium The mechanism by which HRT affects GI tissues is not well understood.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently used hormone replacement therapy consists of estrogen pills for hysterectomized women and estrogen-progestin combinations for the rest [19,20]. Estrogen helps alleviate menopausal symptoms, while progestin prevents estrogen-induced proliferation of uterine epithelium The mechanism by which HRT affects GI tissues is not well understood.…”
Section: Discussionmentioning
confidence: 99%
“…While some studies showed that estrogen promotes malignancy by stimulating growth of cells like bladder and gastric tissues, others noted that it delays progression of EOC and melanoma [19]. To note, estrogen-progestin combination was associated with a higher risk of breast cancer compared to estrogen-only HRT, raising questions around the role of progestin in the development of cancer [20].…”
Section: Discussionmentioning
confidence: 99%
“…17 Evidências apontam que o uso de estrogênio pode estimular a proliferação celular maligna em alguns casos, mas retardar em outros. 16 Kohn et al 8 realizaram uma revisão de literatura em que o estrogênio isolado foi utilizado como forma de tratamento para os sintomas climatéricos. Essa terapia apresentou uma melhora nos sintomas sexuais e geniturinários, como ondas de calor, sudorese noturna, rubor e atrofia vulvovaginal e sintomas vasomotores.…”
Section: Estratégia De Buscaunclassified
“…Symptoms of vulvovaginal atrophy or genitourinary syndrome of menopause occur secondary to oestrogen deficiency caused by different cancer therapies (radiotherapy, chemotherapy, and surgery. 1 The genitourinary syndrome of menopause (GSM) is a newer nomenclature for the condition previously known as vulvovaginal atrophy. It is characterized by a constellation of signs and symptoms resulting from diminished oestrogen.…”
Section: Introductionmentioning
confidence: 99%